PIDANA MATI PERSPEKTIF HUKUM ISLAM: ANTARA KEADILAN DAN HAK ASASI MANUSIA - Dalle, Jumarni; Hasan, Hamzah; Haddade, Abdul Wahid (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
The death penalty in Islamic law holds significant importance as a form of justice for serious crimes such as intentional murder, adultery by a married person, robbery, apostasy, and rebellion. From the perspective of Islamic law, the death penalty is not only intended to serve as a deterrent but also as a means to uphold justice for the victim, the victim’s family, and society at large. While there are views that associate the death penalty with violations of human rights, in Islamic law, its application is based on the principle of justice, which must be proportionate to the crime committed, while considering the public benefit. The application of the death penalty, whether as hudud, qishash, or ta'zir, demonstrates that justice in Islam is not only retributive but also preventive, aimed at maintaining social balance. This study aims to examine the application of the death penalty in Islamic law from the perspectives of justice and human rights. The findings show that the death penalty serves as an instrument of justice that protects the rights of society and victims from the threat of serious crimes, while upholding the principles of justice and public benefit in its implementation.